INTEGRATION OF RELIGIOUS MODERATION IN EDUCATIONAL LEADERSHIP: EFFORTS TO BUILD STUDENT CHARACTER THROUGH ISLAMIC RELIGIOUS EDUCATION (PAI) - Sabran, Sabran; Al Anshori, Habib Anwar; Zamroni, Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines the integration of religious moderation values in educational leadership in Samarinda, with the aim of encouraging student character development through Islamic Religious Education (PAI). Educational leaders play an important role in instilling the values of religious moderation in the school environment, which involves promoting tolerance, inclusivity and respect for diversity. This research uses a qualitative approach, using interviews, observations, and document analysis to explore the strategies used by PAI school leaders and teachers to integrate these values into the curriculum and daily school activities. Research findings indicate that inclusive leadership practices significantly influence the acceptance of diverse beliefs among students, reduce the potential for extremism, and promote a balanced religious perspective. Furthermore, this research highlights specific pedagogical strategies that effectively integrate the values of religious moderation, emphasizing character-building values such as empathy, cooperation, and understanding. By integrating the values of moderation into religious education, school leaders not only support national unity and social cohesion, but also contribute to the holistic character development of students. This research emphasizes the importance of leadership in promoting cultural and ethical education and provides practical insights for policy makers, educational leaders, and PAI practitioners who aim to strengthen character education through religious moderation